Straight edge : clean-living youth, hardcore punk, and social change - Haenfler, Ross (Rutgers University Press, 2006)
Straight edge is a clean-living youth movement that emerged from the punk rock subculture in the early 1980s. Its basic tenets promote a drug-free, tobacco-free, and sexually responsible lifestyle-tenets that, on the surface, seem counter to those typical of teenage rebellion. For many straight-edge kids, however, being clean and sober was (and still is) the ultimate expression of resistance-resistance to the consumerist and self-indulgent ethos that defines mainstream U.S. culture. In this first in-depth sociological analysis of the movement, Ross Haenfler follows the lives of dozens of strai.